ALTERNATIVE TOOLS FOR MOTIVATING YOUNG PRIMARY SCHOOL STUDENTS WHEN LEARNING MATHS - Vinkler, Lidija (Journal of process management and new technologies, 2020)
A decrease in concentration, motivation and academic success is a common occurrence with elementary school pupils. This is most noticeable in STEM lessons, particularly in Maths. Teachers resort to various teaching approaches in order to motivate students. However, teachers often realize such approaches bring no significant success in the classroom due to a lack of interest on the part of the students. The motivation and success of students can be increased by grouping the students within heterogeneous classes, which is frequently used with younger elementary school students.The article features a description of three different activities, which can be used to make Maths lessons more appealing when given to students in groups. At first, the activities might not seem related to Maths, but try them as they are great examples of activities, which increase mathematical thought. Described activities are Mud Town, Map Colouring and Ice Cream Stands.
Keywords: didactic approaches; grouping pupils; heterogeneous class; Ice cream Stands; Map Colouring; mathematic class; motivation; Mud Town